Dust emissions from undisturbed and disturbed soils: effects of off-road military vehicles - Xu, Youjie (Kansas State University, 2014)
Military training lands can be significant sources of fugitive dust emissions due to wind erosion. This study was conducted to determine dust emission potential of soils due to wind erosion as affected by off-road military vehicle disturbance. Multi-pass traffic experiments using two types of vehicles (i.e., wheeled and tracked) were conducted on six soil textures at four military training facilities: Fort Riley, KS; Fort Benning, GA; Yakima Training Center, WA; and White Sands Missile Range (WSMR), NM. Prior to and after the preselected number of vehicle passes, soil samples at three locations were collected with minimum disturbance into trays. Adjacent to the location where tray samples were collected, a Portable In-Situ Wind Erosion Lab (PI-SWERL) was used to measure dust emission potential. The tray samples were tested in a laboratory wind tunnel (with sand abrader) for dust emission potential using a GRIMM aerosol spectrometer and gravimetric method with filters. Comparison of the PI-SWERL (with DustTrak™ dust monitor) and wind tunnel (with GRIMM aerosol spectrometer) measurement results showed significant difference in measured values but high correlation, particularly for soils with high sand content. Wind tunnel tests results showed that sampling locations significantly affected dust emissions for the tracked vehicles but not for the light-wheeled and heavy-wheeled vehicles. Also, soil texture, number of vehicle passes, and vehicle type significantly affected dust emissions. For the light-wheeled vehicles, dust emissions increased as the number of vehicle passes increased. From undisturbed conditions to 10 vehicle passes, there was a significant (P<0.05) increase in dust emissions (297%) on average for all light-wheeled vehicle tests. From 10 to 25 passes and 25 to 50 passes, an additional 52% and 62% increments were observed. For the tracked vehicle, for the straight section sampling location, dust emission increased as the number of vehicle passes increased. However, for the curve section, dust emissions at any level of pass were significantly higher than initial condition; beyond the first pass, no significant increase was observed.
Keywords: wind erosion; soil; saltation impact; particulate matter; Engineering, Agricultural (0539); Environmental Engineering (0775); Environmental Studies (0477)